Stressors for farmworker parents during wildfire season - Savannah M D'Evelyn; Isabel Nerenberg; Maria Blancas; Laura Rivera; Alyssa Suarez; Dennise O Drury; Edward J Kasner (BMC, 2024)
Abstract Background The severity of wildfire seasons amplify stressors that farmworker families in the Pacific Northwest face as they balance childcare, work, and personal wellbeing. A lack of safe and attainable childcare has been a challenge for farmworker parents since before the Covid-19 pandemic and is of particular concern during wildfire season when parents must weigh the risks and benefits of leaving children at home, taking them to work, or sending them to childcare. This study describes how stressors of balancing childcare, work, and concerns about children's exposure to smoke during wildfire season impact the wellbeing and workplace absenteeism and presenteeism for farmworker parents. Methods To understand the impact of this balancing act on farmworker parents, researchers from the University of Washington partnered with Wenatchee's Community for the Advancement of Family Education to conduct interviews with 20 farmworker parents, and co-host two town hall discussion meetings within the community. Results Six qualitative themes emerged from our interviews including that farmworker parents feel both ill-prepared at home to protect their families, and also do not feel as though they are being provided with adequate resources at work to protect their own personal health. Through the town hall events, we learned that verbal messaging and storytelling are effective and appreciated routes of communication. Conclusions Overall, we found that messaging and effective communication around how to prepare for the worsening levels of smoke is lacking among the farmworker community. Future research will address the messaging and communication gaps that must be filled to protect the health of both workers and their families during smoke season and beyond.